KEPENTINGAN AUSTRALIA DALAM PENCARIAN PESAWAT MALAYSIA AIRLINES MH370 DI SAMUDRA HINDIA SELATAN - Saraswati, Ida Ayu Gita; Sushanti, Sukma; Widya Nugraha, A. A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research aims to describe Australia's national interests in searching for Malaysia Airlines MH370 in the South Indian Ocean. Malaysia Airlines Flight MH370 disappeared on 8 March 2014 en route from Kuala Lumpur to Beijing. All the available data indicates the aircraft crashed in the Southern Indian Ocean.The Australian Government agreed to take the responsibility of leading and coordinating the search efforts in the Southern Indian Ocean.This research used qualitative descriptive methods to analyze the issues.This issue discussed by answering the question about Australia’s national interest in the search of Malaysia Airlines MH370 in the Southern Indian Ocean. This research used collected data from various sources including,literary sources, news and reports. Data were analyzed with the concept of national interest in international relations.The result of the analysis showed Australia's interest in gaining trust, legitimacy and improving its status and proximity to the Asian region. Keywords:Australia, MH370, National Interest